2014
DOI: 10.1186/1471-2229-14-13
|View full text |Cite
|
Sign up to set email alerts
|

Silicon mitigates heavy metal stress by regulating P-type heavy metal ATPases, Oryza sativalow silicon genes, and endogenous phytohormones

Abstract: BackgroundSilicon (Si) application has been known to enhance the tolerance of plants against abiotic stresses. However, the protective mechanism of Si under heavy metals contamination is poorly understood. The aim of this study was to assess the role of Si in counteracting toxicity due to cadmium (Cd) and copper (Cu) in rice plants (Oryza sativa).ResultsSi significantly improved the growth and biomass of rice plants and reduced the toxic effects of Cd/Cu after different stress periods. Si treatment ameliorated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
157
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(182 citation statements)
references
References 69 publications
19
157
2
4
Order By: Relevance
“…The accumulated silicon in rice leaves improves photomorphogenesis, which in turn, increases the photosynthetic rate and also strengthens the cuticle membranes. The provision of additional Si to the rice plant promotes growth parameters such as length, weight, and chlorophyll contents (Kim et al 2014a). Similar effects have also been reported in soybeans, cotton, poinsettia, wheat, maize, rice, sorghum cucumber, and tomatoes (Li et al 1989;McAvoy and Bible 1996;Gong et al 2005;Hattori et al 2005;Liang et al 2005;Feng et al 2009;Hamayun et al 2010;Kim et al 2011;Kim et al 2014b, c).…”
mentioning
confidence: 49%
See 2 more Smart Citations
“…The accumulated silicon in rice leaves improves photomorphogenesis, which in turn, increases the photosynthetic rate and also strengthens the cuticle membranes. The provision of additional Si to the rice plant promotes growth parameters such as length, weight, and chlorophyll contents (Kim et al 2014a). Similar effects have also been reported in soybeans, cotton, poinsettia, wheat, maize, rice, sorghum cucumber, and tomatoes (Li et al 1989;McAvoy and Bible 1996;Gong et al 2005;Hattori et al 2005;Liang et al 2005;Feng et al 2009;Hamayun et al 2010;Kim et al 2011;Kim et al 2014b, c).…”
mentioning
confidence: 49%
“…Si is a major constituent of many plants, but is not generally classified as 'essential'; although Si is regarded as an essential element in a number of species of the Poaceae and Cyperaceae, it has not been possible to demonstrate that it is essential to all higher plants because direct evidence is still lacking (Epstein 1994;1999;Liang et al 2007). Previous research has reported that exogenous Si can increase plant tolerance to high manganese concentrations (Horst and Marschner 1978), drought (Lux et al 2002), heavy-metal contamination (Neumann and zur Nieden 2001;Kim et al 2014a), and resistance to pests and pathogens (Belanger et al 2003;Liang et al 2007;Richmond and Sussman, 2003). Furthermore, Si contributes to stress resistance in other crops such as the cucumber (Zhu et al 2004), soybean (Hamayun et al 2010), tomato (Heine et al 2007), and wheat (Gong et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has suggested that silicon (Si) fertilizers are effective in reducing the concentration of Cd (Shi et al 2005;Kim et al 2014) or As in rice grain (Guo et al 2007;Seyfferth and Fendorf 2012). Various Si compounds, such as K 2 SiO 3 and silica gel, were chosen as Si fertilizers for hydroponic culture or pot experiments to mitigate Cd or As individually in rice shoots (Zhang et al 2008;Putwattana et al 2010;Marmiroli et al 2014).…”
Section: Responsible Editor: Elena Maestrimentioning
confidence: 99%
“…O Si é benéfico às plantas por garantir a proteção contra múltiplos fatores bióticos e abióticos (MA, 2004). Entre os efeitos benéficos do Si estão a maior resistência ao estresse hídrico (LIANG et al, 2007), às doenças (RESENDE et al, 2009;ARSENAULT-LABRECQUE et al, 2012;RESENDE et al, 2013), às pragas (KORNDÖRFER et al, 2011;KEEPING et al, 2013;DIAS et al, 2014) e maior tolerância aos metais pesados que prejudicam o desenvolvimento das plantas (WU et al, 2013;KIM et al, 2014;PONTIGO et al, 2015).…”
unclassified